ØªØ£Ø«ÙŠØ± Ø§Ù„Ù…ÙØ±Ø¯Ø§Øª Ù…Ù† ÙˆØ³Ø§Ø¦Ù„ Ø§Ù„ØµÙˆØ±Ø© ÙÙŠ ØªØ±Ù‚ÙŠØ© Ù…Ù‡Ø§Ø±Ø©Ø§Ù„ÙƒÙ„Ø§Ù… Ø¹Ù„ÙŠØ·Ù„Ø§Ø¨ - asriandi asriandi; Hikmah Hikmah (Lughatu Ad-Dhat, 2021)
The purpose of this study was to determine the extent of the effect of the vocabulary of the means of Al Sawar in the promotion of speech skill on the students of the second semester of the Islamic Secondary School of Bibides with a total of 20 students. Based on the student learning test results data, the average value of learning outcomes appears in the pre-test 6.9 and after the selection 7.1, and the test results show that the relationship between the pre-test and the post-test is strong and important, so that it can be concluded that the effect of the media and images in upgrading the skill Speech is for students and worth using it to learn Arabic. Regarding the results of the